(untitled) (Nativa, 2023)
En este estudio se desenvolvieron redes neuronales artificiales para predecir el conforto térmico animal, en función de la temperatura ambiente y la velocidad del aire para cada día del año en el calendario juliano. Los datos fueron obtenidos en el sitio del Instituto Nacional de Meteorología para una serie histórica de 30 años, coleccionada en la Estación Convencional Padre Ricardo Remetter, municipio de Santo Antonio de Leverger-MT. Para la elaboración de las redes se adoptó como variable de entrada el día del año y como variable de salida la carga térmica de radiación. El número de neuronas varió entre 2 y 15, utilizándose una y dos camadas ocultas. El ajuste de las redes se verificó por el coeficiente de determinación, error absoluto medio, porcentaje medio del error absoluto, la normalidad de los residuos y la prueba de t-Student. No hubo discrepancias entre los valores estimados por las redes y los obtenidos de la serie histórica. Finalmente se seleccionaron diez arquitecturas con adecuados índices de desempeño y las cuatro mejores se sometieron al análisis de residuos. Se concluyó que las redes neuronales del tipo perceptron con dos camadas ocultas fueron apropiadas para pronosticar la carga térmica radiante, conforme el día Juliano. Palabras-clave: conforto térmico; red neuronal artificial; series temporales. Annual prognostic of the radiant thermal using artificial intelligence ABSTRACT: In this research, artificial neural networks were developed to predict the animal thermal comfort based on the room temperature and air velocity for the year day in the Julian calendar. The data were obtained from the website of the National Institute of Meteorology for a 30-year historical series, collected at the Padre Ricardo Remetter Meteorological Station, municipality of Santo Antônio de Leverger-MT. To elaborate the networks, the day of the year was adopted as the input variable and the radiation thermal load as the output variable. The number of neurons ranged varied from 2 to 15, being used one and two hidden layers. The adjustment of the networks was verified by the determination coefficient, mean absolute error, mean percentage of the absolute error, the normality of residues and the t-Student test. The values estimated by the networks and those obtained from the historical series did not differ. Finally, ten architectures with adequate performance and efficiency indexes were selected and among them the four best were submitted to the residue analysis. It was concluded that the artificial perceptron neural networks formed by two-layer hidden were suitable for the prognosis of the radiant thermal load, as a function of Julian day. Keywords: thermal comfort; artificial network; time series.